2022
DOI: 10.1038/s41598-022-14104-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the HERV-derived cell-fusion inhibitor, suppressyn, in the fusion defects characteristic of the trisomy 21 placenta

Abstract: Suppressyn (SUPYN) is the first host-cell encoded mammalian protein shown to inhibit cell–cell fusion. Its expression is restricted to the placenta, where it negatively regulates syncytia formation in villi. Since its chromosomal localization overlaps with the Down syndrome critical region and the TS21 placenta is characterized by delayed maturation of cytotrophoblast cells and reduced syncytialization, we hypothesized a potential link between changes in SUPYN expression and morphologic abnormalities in the TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…This result suggests that if SUPYN acts by receptor interference, its interaction with ASCT2 leads to partial receptor degradation, which is consistent with some instances of receptor interference ( 22 , 23 ). In agreement with previous observations ( 6 , 24 ), we noted that SUPYN knockdown in Jar cells resulted in selective loss of a putative unglycosylated isoform of ASCT2 (fig. S11, B to D).…”
supporting
confidence: 93%
“…This result suggests that if SUPYN acts by receptor interference, its interaction with ASCT2 leads to partial receptor degradation, which is consistent with some instances of receptor interference ( 22 , 23 ). In agreement with previous observations ( 6 , 24 ), we noted that SUPYN knockdown in Jar cells resulted in selective loss of a putative unglycosylated isoform of ASCT2 (fig. S11, B to D).…”
supporting
confidence: 93%
“…In trisomy 21 placenta, the number of Suppressyn-positive cytotrophoblasts increased, and the expression level of Suppressyn per cytotrophoblast also increased [19]. The expression level of Suppressyn in the serum is elevated in trisomy 21, resulting in excessive suppression of placental formation and immature placenta [19].…”
Section: Erv Abnormalities and Placenta-associated Diseasesmentioning
confidence: 99%
“…In addition, cell-cell fusion is disrupted in the placenta of trisomy 21 (Down syndrome) owing to the abnormal expression of Syncytin-2, resulting in dysplasia of the syncytiotrophoblast [112,113]. In trisomy 21 placenta, the number of Suppressyn-positive cytotrophoblasts increased, and the expression level of Suppressyn per cytotrophoblast also increased [19]. The expression level of Suppressyn in the serum is elevated in trisomy 21, resulting in excessive suppression of placental formation and immature placenta [19].…”
Section: Erv Abnormalities and Placenta-associated Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of placenta formation Sugimoto and colleagues demonstrated that the human endogenous retroviral (HERV) element suppressyn impaired syncytin-1-mediated cytotrophoblast fusion by binding to the syncytin-1 receptor alanine, serine, cysteine transporter 2 (ASCT2) [ 79 ]. Moreover, increased suppressyn serum levels were found in women with placental defects in Down syndrome pregnancies [ 80 ]. In fact, a disturbed or dysregulated trophoblast syncytialization during placentation is commonly associated with an impaired maintenance and failed integrity of the blood-placental barrier.…”
Section: Similarities Between Physiological and Patho-physiological C...mentioning
confidence: 99%